2015
DOI: 10.4103/2229-3485.148819
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of honey, chlorhexidine gluconate (0.2%) and combination of xylitol and chlorhexidine mouthwash (0.2%) on the clinical level of dental plaque: A 30 days randomized control trial

Abstract: Aim:To compare the effect of honey, chlorhexidine mouthwash and combination of xylitol chewing gum and chlorhexidine mouthwash on the dental plaque level.Materials and Methods:Ninety healthy dental students, both male and female, aged between 21 to 25 years participated in the study. The subjects were randomly divided into three groups, i.e. the honey group, the chlorhexidine gluconate mouthwash group and the combination of xylitol chewing gum and chlorhexidine (CHX) mouthwash group. The data was collected at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 15 publications
1
30
2
Order By: Relevance
“…In 2015, Jain et al investigated the effects of honey, CHX mouthwash, and Xylitol chewing gum plus CHX mouthwash in vivo on the plaque surface; they concluded that the honey group and the CHX plus Xylitol group were more effective in decreasing the plaques. (32) The cited study describes the reduction in dental plaque following honey use, which is inconsistent with our study that showed a direct reduction in the number of cariogenic microorganisms, but since there are different cariogenic microorganisms in dental plaque, their study also confirms the antimicrobial properties of honey in line with our study.…”
Section: Discussioncontrasting
confidence: 99%
“…In 2015, Jain et al investigated the effects of honey, CHX mouthwash, and Xylitol chewing gum plus CHX mouthwash in vivo on the plaque surface; they concluded that the honey group and the CHX plus Xylitol group were more effective in decreasing the plaques. (32) The cited study describes the reduction in dental plaque following honey use, which is inconsistent with our study that showed a direct reduction in the number of cariogenic microorganisms, but since there are different cariogenic microorganisms in dental plaque, their study also confirms the antimicrobial properties of honey in line with our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Use of CAM therapies is growing in the general population as a preventive and therapeutic modality. [25][26][27][28][29][30][31][32][33][34][35][36] Including CAM education into the dentist curriculum can increase their awareness of MSD prevention from student life itself. Future research that looks at incorporating CAM therapies such as yoga, meditation, acupuncture, and acupressure into dental programs can assess their effectiveness by evaluating dentists' musculoskeletal pain once they are in private practice.…”
Section: Discussionmentioning
confidence: 99%
“…This further supports evidence that the application of honey to the inside of the oral cavity is effective in reducing the pathogenic bacteria that cause dental caries, and has a positive effect on plaque levels and gingivitis. 17,41,42 These findings demonstrate that the use of honey in future studies is safe for the dental health of participants. It was also proposed that similar trials comparing two intervention groups of Manuka and conventional honey should be completed 18 ; however, given…”
Section: Adverse Effectsmentioning
confidence: 73%